IMMUNOMODULATORY OF Bifidobacterium breve AND INHIBITORY EFFECT OF BIFIDOBREVICIN -LHM ON Streptococcus agalactiae AND ITS β-HEMOLYSIN - H. Mahdi, L. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The objective of this research was production, purification and characterization of Bifidobrevicin-LHM from Bifidobacterium breve isolated from women breast Colostrum. The antibacterial activity of crude and purified Bifidobrevicin-LHM on Streptococcus.agalactiae were assayed, also investigated their effect on β-hemolysin activity which is purified from S.agalactiae in vitro .We developed an untried mouse model of acute S.agalactae pneumonia, biochemical, histopathological, microbiological, innate and specific immune response were determined. Purified and crude Bifidobrevicin-LHM exhibited bactericidal action against S.agalactiae isolates and its β-hemolysin activity in vitro. Oral and Intranasal administration of B. breve post infection leading to significantly increase S.agalactae clearance rates in lung and blood, reduce the BAL albumin concentration,lung injury and Lactate dehydrogenase activity, enhanced production of Interleukein 10,IL-4 and high level of BAL -anti S.agalactiae IGg compared with control P<0.05 .To our knowledge the present research is the first report on purification and characterization of bacteriocin produced by B.breve exhibiting inhibitory activity on S.agalactiae and its β-hemolysin. Bifidobrevicin-LHM can inhibit virulence in S.agalactiae is an alternative select for therapy, taking into consideration that orally and intranasally administered.B. breve stimulate both the specific and innate immune response in the respiratory tract. These end results recommend that specific immunomodulatory properties of B. breve should be characterized when developing clinical application